Impacto jurídico del anticipo del impuesto a la renta, aplicado como impuesto mínimo presuntivo. - Vega Ramírez, Patricia (2011)
In this paper we show the results of the investigation, on the current calculation of advance income tax in Ecuador, how much the formula affects taxpayers and the possibility of make this advance in a final tax if payment is in excess of what is ultimately declared and paid at the tax year end. The study begins with the treatment of criteria bearing on tax matters, the analysis of the financial activity of Ecuador, its nature, evolution and budget revenue and expenditure. Theoretical concepts of financial law were collected, also for tributary aspects and further discussion at the various branches of tax law. Then we move on to the study of tax law principles, both constitutional as set forth in the Code Tax, both have in common to determine the tasks for the Tax Administration and the taxpayers' bound to the State, either voluntary or coercive penalty. Throughout the remaining chapters we developed the aspects related to Ecuadorian domestic taxation, the tax liability related to the birth and enforceability of taxes, subjects involved and the ways to extinguish the obligation. During the investigation of this example we analyzed each power of the tax administration: law enforcement, determinant, decisive, penalizing and tax collector. Then we got deeper into the review of income tax, the object, the aim of the taxable event, the rates, the subjects, form and date of statement, the withholding of income tax and more carefully on the subject of study: Advance Income Tax, its evolution, its method of calculation, who are obligated to, the economic incidence, etc. Then we performed a comparative analysis of tax laws from Chile and Peru, and then the differences between the respective so called accounts payments, advance payment of income tax, how to be establish, set the dates of payment and compensation or refund of excess payment if any, once declared the annual income tax. The field research could confirm us the initial hypothesis and we verify the proposed objectives. The results led us to reach conclusions and recommendations, which in essential led us to propose a reform to Article 41 of the Internal Tax Regime Law, which eliminates the tax payment income, as final payment or presumptive minimum income. This reform will be able to avoid the punishment for the operations related to the activities responsible for generating the income and ensure that there will not be violations to the principles of taxation.